1972
DOI: 10.1152/ajplegacy.1972.223.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluoride on metabolism and mechanical properties of rat bone

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1974
1974
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…He concludes that the fluoride could not prevent bone disappearance in rats as an effect of the calcium difficiency in the food. Wolinsky et al (1972) found in a similar study of whole rat femur tested in bending a decrease in breaking strength and elastic stiffness at 500 ppm dose level compared to controls (5 ppm) but no change in energy absorption to the breaking point. In a study of the whole rabbit femur Faccini (1969) found an increase in strength as an effect of fluoride but concluded that this was due to an increase in the width of the cortex and not to a change of the quality of bone, breaking and elasticity being in fact significantly reduced.…”
Section: In Humansmentioning
confidence: 60%
See 1 more Smart Citation
“…He concludes that the fluoride could not prevent bone disappearance in rats as an effect of the calcium difficiency in the food. Wolinsky et al (1972) found in a similar study of whole rat femur tested in bending a decrease in breaking strength and elastic stiffness at 500 ppm dose level compared to controls (5 ppm) but no change in energy absorption to the breaking point. In a study of the whole rabbit femur Faccini (1969) found an increase in strength as an effect of fluoride but concluded that this was due to an increase in the width of the cortex and not to a change of the quality of bone, breaking and elasticity being in fact significantly reduced.…”
Section: In Humansmentioning
confidence: 60%
“…Wolinsky et al (1972) found on the other hand a decreasing bending strength and elastic stiffness at high dose level (500 ppm). Similar findings were earlier presented by Jovanovits (1944) with decreased breaking strength and elastic stiffness with increasing doses and time of fluoride addition.…”
Section: Summary Of Effects Of Fluoride Additionmentioning
confidence: 85%
“…A similar controversy is found in epidemiological reports on the effects of water fluoridation on the incidence of hip fractures (19)(20)(21). In animal studies, where biomechanical data are available, NaF was reported to increase (22), decrease (23)(24)(25), or have no effect on bone strength (26)(27)(28). Short-term studies in ewes showed that at a low dose NaF stimulates bone formation by increasing the recruitment and lifespan of osteoblasts; at higher doses, NaF decreased osteoblast activity (29).…”
Section: Introductionmentioning
confidence: 63%
“…The accretion of bone in response to fluoride therapy has been documented in the vertebrae by bone density measurements (8,10,48) and in cancellous bone by iliac crest biopsies (49). Several animal studies using mechanical testing have shown a deterioration in bone "quality" with increased bone fluoride content (23)(24)(25)(26)33). Another therapy, which raised questions regarding the correlation of bone mass and fracture incidence, is treatment with the bisphosphonate etidronate (EHDP).…”
Section: Discussionmentioning
confidence: 99%
“…The entire fresh, right femurs of the animals were used in breaking strength studies, the left femur employed for chemical measurements. The preparation of bone tissue, determina tions of dry weight, ash, calcium and phosphorus, and the instrumentation and calculations of mechanical parameters have been described previously (16). Ultimate stress is the maximum stress a material will sustain at failure; modulus of elasticity is the measure of the stiffness of the material, i .e.…”
Section: Methodsmentioning
confidence: 99%